2023
DOI: 10.1002/pc.27227
|View full text |Cite
|
Sign up to set email alerts
|

Creep properties and damage mechanism of molded glass fiber reinforced plastic

Abstract: Glass fiber reinforced plastic (GFRP) has become one of the most commonly used materials in the structure of aero engines in the last decades. In this study, GFRP was fabricated by molding with phenolic resin as the matrix. Specimens were prepared along horizontal and vertical directions. Fiber distribution, tensile properties, long‐term creep performance, and damage mechanism were systematically investigated. Experimental results shows that horizontal specimens have better tensile properties, lower viscoelast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…In addition, some specific loading scenarios necessitate higher failure strains, and this can be achieved through off-axis fiber orientations. 8,9 Notable instances of such structural customizations are evident in the Rockwell High Maneuverability Aircraft Technology and the Grumman X29 Forward-Swept Wing Demonstrators aircraft. 10 Thus, a deeper insight should be taken to investigate the off-axis compression properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some specific loading scenarios necessitate higher failure strains, and this can be achieved through off-axis fiber orientations. 8,9 Notable instances of such structural customizations are evident in the Rockwell High Maneuverability Aircraft Technology and the Grumman X29 Forward-Swept Wing Demonstrators aircraft. 10 Thus, a deeper insight should be taken to investigate the off-axis compression properties.…”
Section: Introductionmentioning
confidence: 99%
“…The change in direction will indirectly affect the service performance of the structure. In addition, some specific loading scenarios necessitate higher failure strains, and this can be achieved through off‐axis fiber orientations 8,9 . Notable instances of such structural customizations are evident in the Rockwell High Maneuverability Aircraft Technology and the Grumman X29 Forward‐Swept Wing Demonstrators aircraft 10 .…”
Section: Introductionmentioning
confidence: 99%
“…[12] The existing ionogel-based sensors are limited by small working range, single response mode, and the ability to achieve self-powered sensing. [13] Therefore, it is still a great challenge to develop ionogels with a comprehensive performance in multifunctionality for next generation self-powered ionic skin (Iskin).…”
Section: Introductionmentioning
confidence: 99%
“…Uomoto et al [29] found that the creep deformation of GFRP rebars is large when the sustained stress level reaches 80% of the ultimate strength of the GFRP rebars. Guowei Li et al [30,31] found that GFRP creep occurs only when the load level reaches 77% of the ultimate load, but creep deformation of GFRP was not found in the experiment, indicating that GFRP has excellent creep resistance under the effect of a long-term low load level, which is consistent with the results of Qi Sun [32]. Yihua Cui et al [33] concluded that the interaction of glass fiber, wood powder, and plastic formed a stable three-dimensional spatial structure, which existed in the plastic matrix as a strong skeleton and prevented the generation and expansion of cracks, thus improving the mechanical strength and impact resistance of the composites; the mechanical properties of WPCs show a trend of increasing and then decreasing with an increase in glass fiber content.…”
Section: Introductionmentioning
confidence: 99%